A Rare Case of Periprosthetic Streptobacillosis - Rapid Identification via Nanopore Sequencing after Inconclusive VITEK MS Results - Spott, Riccardo; Schleenvoigt, Benjamin T; Edel, Birgit; Pletz, Mathias W; Brandt, Christian (Archives of Clinical and Medical Case Reports, 2022)
Streptobacillus moniliformis is the main cause of human streptobacillosis, also known as rat-bite or Haverhill fever. A correct diagnosis might be delayed due to scarcity, non-specific symptoms, and difficulties in cultivating this fastidious organism. We report on an 85-year-old man with periprosthetic streptobacillosis, which manifested itself in the form of immobilizing hip pain in the left prosthetic hip joint. The patient denied fever, chills, and night sweats. No fraction of the left hip could be detected via x-ray. Punctuatio.n of the hip joint revealed putrid aspirate and computer tomography detected an abscess in the left hip. From the synovial fluid and from concomitantly drawn blood cultures grew a pleomorphic, gramnegative rod after 48 h and 35 h, respectively. The VITEK and VITEK MS (MALDI-TOF) analysis remained inconclusive. Therefore, the unknown isolate was sequenced using Nanopore Third-Generation Sequencing. After one hour enough data were generated to identify the microorganism as Streptobacillus moniliformis. To date, this is the first published case of identifying Streptobacillus moniliformis by rapid whole genome sequencing as the cause of a periprosthetic infection. Despite a mortality rate of around 10% in humans, streptobacillosis is rarely diagnosed and published. In this context, nanopore sequencing enabled fast and reliable diagnostic results for identifying microorganisms and their properties